Literacy and Software Features in Foreign Language Teaching - Li, Yiran; Medic, Branko (The journal of contemporary issues in business and government, 2021)
The digital world permeates every aspect of our lives. We use our phones and laptops for several hours each day. We watch television to relax and connect with our wider social network using the internet. It‟s only natural then, that digital technologies are becoming more and more embedded within classrooms. Teachers have found that, when used purposefully, technology can be a useful tool to enhance learning outcomes. As a foreign language teacher for college age students, I choose to use digital technologies in a mindful, meaningful way. I have found that blogs and wikis can play a powerful role in enhancing my student‟s written language skills and their collaboration with each other. Another digital medium that I recognize that can play a large role in enhancing my students‟ foreign language learning is videos. The visual format of videos allows students to pick up from visual cues and connect the words that are being spoken to meaning thereby building on students‟ vocabulary in the language the video is in. When captions are activated, students can either use subtitles to build on their reading skills or read the subtitles in their own language to understand better about what is happening As a teacher whose practices are informed by pedagogy, theory and research, I recognise that it is important to look to relevant academic literature to help me design my curriculum and teaching plans. While I practically and instinctively recognise the benefits of videos on foreign language learning, I have undertaken a literature review to help deepen my pedagogical knowledge. In this paper, I conduct a literature review and evaluate how findings of this review reposition my perspectives and will further impact my practices.